FORMATION OF CREATIVE POTENTIAL OF STUDENTS BASED ON INNOVATIVE APPROACHES - Rizakhojayeva G.A.; Akeshova M.M.; Shaikhystamova M.B.; Jabbarova S. (Scientific Journal of Pedagogy and Economics, 2021)
In the context of the reform and modernization of education in Kazakhstan and the accession of the Republic of Kazakhstan to the Bologna process, Akhmet Yassawi International Kazakh-Turkish University has aimed to train specialists of an international level and improve the quality of education, the main course is to develop new pedagogical grounds for the formation of a future specialist both as a professional and as a creative person with creative potential and professional-creative competence. The search for personnel reserves to improve the professional training of future specialists is shifting to the development of creative potential and communicative competence. There is a need to transform the educational environment of higher education into a single creatively developing educational space that promotes the formation and development of students' creative potential and competence as a factor in successful self-realization in the profession and the prerequisites for competent support for the creative development of students.